(untitled) (International Journal of Engineering and Computer Science, 2015)
Wireless sensor network is a self-organized wireless network system constituted by numbers of energy-limited micro sensors under the banner of industrial application (IA). In this project, a secure and efficient cost aware securer routing protocol to address two conflicting issues: they are lifetime optimization and security. Through the energy balance control and random walking the conflicting issues are addressed. Then discover the energy consumption, is severely disproportional to the uniform energy deployment for the given network topology, which greatly reduces the lifetime of the sensor networks. To solve this problem an efficient non-uniform energy deployment strategy is used to optimize the lifetime and message delivery ratio under the same energy resource and security requirement. It is also to provide a quantitative security analysis on the proposed routing protocol.